Development and characterization of novel ZnO-loaded electrospun membranes for periodontal regeneration - Muenchow, Eliseu A.; Albuquerque, Maria Tereza P. [UNESP]; Zero, Bianca; Kamocki, Krzysztof; Piva, Euandro; Gregory, Richard L.; Bottino, Marco C. (Elsevier B.V., 2015)
Objectives. This study reports on the synthesis, materials characterization, antimicrobial capacity, and cytocompatibility of novel ZnO-loaded membranes for guided tissue/bone regeneration (GTR/GBR). Methods. Poly(epsilon-caprolactone) (PCL) and PCL/gelatin (PCL/GEL) were dissolved in hexafluoropropanol and loaded with ZnO at distinct concentrations: 0 (control), 5, 15, and 30 wt.%. Electrospinning was performed using optimized parameters and the fibers were characterized via scanning and transmission electron microscopies (SEM/TEM), energy dispersive X-ray spectroscopy (EDS), Fourier transform infrared spectroscopy (FTIR), contact angle (CA), mechanical testing, antimicrobial activity against periodontopathogens, and cytotoxicity test using human dental pulp stem cells (hDPSCs). Data were analyzed using ANOVA and Tukey (alpha = 5%). Results. ZnO nanoparticles were successfully incorporated into the overall submicron fibers, which showed fairly good morphology and microstructure. Upon ZnO nanoparticies' incorporation, the PCL and PCL/GEL fibers became thicker and thinner, respectively. All GEL-containing membranes showed lower CA than the PCL-based membranes, which were highly hydrophobic. Overall, the mechanical properties of the membranes were reduced upon ZnO incorporation, except for PCL-based membranes containing ZnO at the 30 wt.% concentration. The presence of GEL enhanced the stretching ability of membranes under wet conditions. All ZnO-containing membranes displayed antibacterial activity against the bacteria tested, which was generally more pronounced with increased ZnO content. All membranes synthesized in this study demonstrated satisfactory cytocompatibility, although the presence of 30 wt.% ZnO led to decreased viability. Significance. Collectively, this study suggests that PCL- and PCL/GEL-based membranes containing a low content of ZnO nanoparticles can potentially function as a biologically safe antimicrobial GTR/GBR membrane. (C) 2015 Academy of Dental Materials. Published by Elsevier Ltd. All rights reserved.
Keywords: Electrospinning; Zinc oxide; Oral bacteria; Periodontal regeneration; Periodontitis; Membranes